Sistem Muskuloskeletal dan Integumen - Achsanul Ghiffari As Syafi; Annisa Nur Agustin; Celsi Olivia; Dwi Novitasari; Keyzia Karinina Mutiara Bintang; Nabila Rahma Nur Aini; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
This study employed a qualitative approach with a literature review, comprising a review of various secondary data sources collected on the musculoskeletal and integumentary systems. The results showed that the musculoskeletal system is a system in the human body that provides stability and enables coordinated movement. Disruption of this system will affect the body's locomotor system. Musculoskeletal injuries can also develop over a longer period of time (chronic), such as back pain due to improper sitting posture while working at a computer